Managing organizations for sport and physical activity a systems perspective - Chelladurai, Packianathan Distinguished Professor (Holcomb Hathaway, Publishers, 2014)
Managing organizations for sport and physical activity, fourth edition, presents a clear and concise treatment of managing organizations in sport and physical activity. The four functions of management-planning, organizing, leading, and evaluating-provide a general framework and the simplest and best introduction to the intricacies of management. For each management function, author Packianathan Chelladurai presents relevant theories and their practical applications, citing theoretical models that are most appropriate to the sports industry's unique aspects. He places organizations in the context of their environment and emphasizes the manager's role in adapting and reacting to changes in the environment. Numerous examples from the fields of physical activity and sport-including professional sports, intercollegiate athletics, health and sports clubs, and recreation/fitness programs-make the book applicable to management careers across various industry segments